THE EFFECTIVENESS OF MOBILE APPS AND ONLINE PLATFORMS IN DEVELOPING ENGLISH SKILLS AMONG SCHOOL STUDENTS - Ziyoda Yaxshiboyeva Juma qizi (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This study explores the effectiveness of mobile applications and online platforms in enhancing English language skills among secondary school students. The research is based on practical teaching experience conducted during an internship at School No. 184. Unlike theoretical studies, this research focuses on real classroom implementation, where digital tools were integrated into daily lessons. A mixed-method approach was applied, including observation, questionnaires, and pre-test/post-test comparison. The findings indicate that mobile apps significantly improve students’ vocabulary acquisition, listening comprehension, and speaking confidence. Moreover, the use of digital tools increases student motivation and classroom participation. However, challenges such as limited internet access and potential distractions were also observed. Overall, the study demonstrates that technology-assisted learning creates a more engaging and effective learning environment when used appropriately.